A dual emission metal–organic framework for rapid ratiometric fluorescence detection of CO32− in seawater. Issue 42 (29th June 2020) - Wei, Yu; Xia, Yan
Abstract : A dual emission metal–organic framework (IRMOF-10-Eu) was prepared and used as a ratiometric fluorescent sensor for CO3 2− detection. Abstract : A dual emission metal–organic framework (IRMOF-10-Eu) was prepared and used as a ratiometric fluorescent sensor for CO3 2− detection. IRMOF-10-Eu had good stability and excellent luminescence in aqueous solution. IRMOF-10-Eu showed dual fluorescence emission from the ligand and Eu 3+ with single excitation. Upon treatment with CO3 2−, the fluorescence ratio ( I 624 / I 358 ) of the probe displayed significant change. The relative fluorescence intensity ratio ( I 624 / I 358 ) and CO3 2− concentration had a linear relationship in 50–300 μM range with a low detection limit of 9.58 μM. And the luminescence probe of CO3 2− showed a fast detection time. The possible mechanism was investigated. CO3 2− changed the structure of IRMOF-10-Eu and interrupted the energy transfer process. Thus, the fluorescence emission intensity of the ligand was increased and Eu 3+ was decreased with the addition of CO3 2− . IRMOF-10-Eu was used to detect CO3 2− in seawater, which showed good prospect in practical application. Subsequently, a highly selective and sensitive probe, IRMOF-10-Eu, may pave an efficient way for CO3 2− detection in seawater.